SUSTAINABLE DESIGN APPROACH: EKSPLORASI LIMBAH DENIM MENGGUNAKAN TEKNIK SASHIKO KEARIFAN LOKAL - Mochammad Charis Hidayahtullah; Ulfah Nafi'ah; Reinny Devi Febryanti Razak; Muhammad Hakim Bintang (Jurnal Desain Indonesia., 2025)
The fast-fashion phenomenon has become one of the largest contributors to global waste, including denim waste. To address this issue various efforts are being undertaken across multiple sectors under the framework of the Sustainable Development Goals (SDGs). Accordingly, this study conducts an experiment to recycle denim waste into new ready-to-use or sellable products, aiming to support one of the SDG categories. The research method used is the Borg & Gall R&D approach, which applies design exploration techniques, such as sashiko techniques from Japan, but uses elements of local Indonesian wisdom. The design process is explained in detail in this article along with the resulting products. Finally, this recycling initiative supports the SDG program under the category “Climate Change Action” and "Responsible Consumption and Production" by offering an alternative solution for managing denim waste and transforming it into economically valuable products. This technique is relatively easy to apply, making it not only a practical approach to addressing denim waste within the framework of the SDGs but also a viable business development recommendation for SMEs in the apparel industry sector.